AC susceptibility in Y1-xTbxCo2 compounds - Pasquevich, A. F. (2004)
AC susceptibility measurements, as a function of temperature and frequency, have been carried out in Y1-xTbxCo2 (0.1 ≤ x ≤ 0.9) compounds to investigate the magnetic phase transition. It is known that YCo2 exhibits very strongly enhanced Pauli paramagnetism, while TbCo2 orders magnetically with a Co moment induced by the Tb molecular field. The phase transition of TbCo2 at 231 K is a second-order phase transition. We found that in Y1-xTb xCo2 the transition changes from first- to second-order as x increases. The increase in the order temperature with Tb concentration is observed and the type of the phase transition is analyzed in the framework of the Inoue-Shimizu model. © 2004 Elsevier B.V. All rights reserved.